Plastic antibody for the diagnosis of acute myocardial infarction - Ricardo, Jacinta (2024)
(Introduction) Novel application Plastic Antibody that responds to a cardiac biomarker, myoglobin (Myo). Imprint stage with electropolymerization of ortho-phenylenediamine (OPD) in the presence of Myo. Template removal from polymeric matrix digested by trypsin. The films acted as biomimetic artificial antibodies and were fabricated on a screen-printed platinium (Pt) electrode (SPE) modified with electroactive Prussian blue nanocubes (PBNCs) to take a step towards disposable sensors for point-of-care applications. The devices showed linear responses to Myo in SWV assays up to 0.01 and 10000 ng/mL.